Examining Teacher Candidates' Psychological Capital Perception Levels in Terms of Certain Variables - Erdoğan TOZOĞLU; Arzu GÜLBAHÇE; Çağatay KASİL; Mücahit DURSUN; Ufuk Han BAĞAÇLI (ümit doğan üstün, 2024)
The objective of the study is to assess the levels of psychological capital perception among teacher candidates with regards to their engagement in sports activities and various other factors. The study was conducted using the relational screening model, with a research group consisting of 337 teacher candidates enrolled at Erzurum Atatürk University Kazım Karabekir Faculty of Education during the 2022-2023 academic year. The research utilized the "Personal Information Form" and "Psychological Capital Perception" scale, which were developed by Atilla and Dönmez (2022), as data collection instruments. During the data analysis, we computed primary descriptive statistics and found that the data exhibited a normal distribution. Parametric tests, such as the t-test and ANOVA, were used because the data followed a normal distribution. The data underwent Cronbach's Alpha analysis to assess its internal consistency values. The Tukey's multiple comparison test was utilized to identify significant disparities among the groups. A correlation analysis was performed to investigate the association between the ages, personal income levels, duration of sporting activities, and Psychological Capital Perception levels of the participants. The results were assessed based on the p-value's significance level of p<.050. The analysis revealed a positive correlation between the participants' ages, personal income levels, duration of sporting activities, and their perception levels of psychological capital. A difference in the participants' perception levels of psychological capital was found between their engagement in different sporting activities and types of sporting activities. The research findings indicate that engaging in sports activities enhances the levels of psychological capital perception among teacher candidates.